Electroinfiltration microfluidic method for deep-sea high-rate lithium ion battery electrode material

Through the electro-immersion microfluidic control method of applying an external electric field between the electrodes of lithium-ion battery, the problem of poor infiltration performance of electrode materials on electrolytes in deep-sea environments is solved, significantly improving the infiltration efficiency and conductivity of the electrodes, and improving the battery's high Power discharge capability.

CN119400928AActive Publication Date: 2025-02-07WUHAN INSTITUTE OF MARINE ELECTRIC PROPULSION (THE 712TH RESEARCH INSTITUTE OF CHINA STATE SHIPBUILDING CORP LTD)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411381194.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

In the deep sea 20-30C high-rate discharge environment, the lithium-ion battery electrode material has poor wetting performance on the electrolyte, resulting in low electrode conductivity and affecting the high-power discharge performance of the battery.

Method used

The electro-immersion microfluidic control method is used to apply an external electric field between the electrodes to regulate the electrostatic interaction between the charge ions in the dielectric layer, improve the interaction between the electrode and the electrolyte, and thereby improve the infiltration efficiency of the electrolyte.

Benefits of technology

The electro-immersion microfluidic control method significantly improves the liquid level climb of the electrolyte in the electrode capillary, enhances the infiltration performance and conductivity of the electrode, and improves the discharge capacity of the deep-sea large-ratio lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a deep-sea high-rate lithium ion battery electrode material electro-infiltration microfluidic method, which comprises the following steps: (1) assembling an electrode material of a lithium ion battery and a diaphragm, and injecting an electrolyte after the assembly is completed; and (2) applying an external electric field between the electrodes to complete infiltration of the lithium ion battery electrode material by the electrolyte. An external electric field is applied between the electrodes by adopting an electro-infiltration microfluidic method, and an induced electric field can appear in the dielectric layer at the interface of the electrodes and the electrolyte, so that the electrostatic interaction among charged ions in the dielectric layer is changed, and the infiltration capacity of the liquid electrolyte in the porous electrode is improved; the wettability between the positive electrode and the negative electrode and the electrolyte is accelerated, the uniform infiltration distribution of the electrolyte in the pole piece is controlled, the infiltration rate of the deep-sea high-rate lithium ion battery electrode material is accelerated, and the method is excellent in infiltration performance and high in efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to an electrowetting microfluidic method for electrode materials of deep-sea high-rate lithium-ion batteries. Background Art

[0002] In deep-sea environments, the pressure can be as high as 100MPa, which is difficult for ordinary commercial lithium-ion batteries to withstand directly; and in order to meet the application of deep-sea environments, the battery is usually required to discharge at a large rate, such as 20-30C, but for batteries working at high power, the wettability of the electrode material to the electrolyte becomes crucial. Wettability refers to the ability of a liquid to spread or penetrate on a solid surface. For batteries, good wettability means that the electrolyte can effectively contact the electrode material, thereby improving the efficiency of ion transfer, which is necessary to ensure the performance of the battery at high power. If the wettability is poor, the electrolyte may not be able to evenly cover the electrode surface, resulting in limited electrochemical reactions in local areas, which in turn affects the overall performance of the battery, especially the electrode conductivity.

[0003] The 20-30C high-rate lithium-ion batteries used in deep-sea applications are usually large-capacity, high-energy-density soft-pack batteries of more than 40Ah. Compared with conventional lithium-ion battery electrodes, they have higher compaction density, thicker electrode thickness, and three-dimensional elastic diaphragms to meet the pressure of 10,000 meters in the deep sea and high-rate discharge performance. Therefore, the electrode requires a longer wetting time during the electrolyte infiltration process, otherwise it will lead to poor wetting performance of the battery electrode material to the electrolyte.

[0004] Therefore, it is necessary to provide a method for improving the wettability of lithium-ion battery electrode materials to solve the problem that the battery electrode materials have poor wettability to the electrolyte in a deep-sea 20-30C high-rate discharge environment, which affects the electrode conductivity of the battery at high power. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies and provide a deep-sea high-rate lithium-ion battery electrode material electro-infiltration microfluidic method to solve the technical problem in the prior art that the battery electrode material has poor wettability or low wetting efficiency for electrolytes in a deep-sea 20-30C high-rate discharge environment.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a microfluidic method for electrowetting of electrode materials for deep-sea high-rate lithium-ion batteries, comprising the following steps: (1) Assemble the electrode material and diaphragm of the lithium-ion battery and inject the electrolyte after the assembly is completed; (2) Apply an external electric field between the electrodes to complete the infiltration of the electrolyte into the lithium-ion battery electrode material.

[0007] Preferably, the voltage of the external electric field is between 100 and 300 mV.

[0008] Preferably, the infiltration time is 2 to 3 hours.

[0009] Preferably, the lithium-ion battery is a lithium iron phosphate soft-pack battery.

[0010] Preferably, the electrolyte comprises a lithium salt and an organic solvent.

[0011] Further preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium bis(trifluoromethylsulfonyl)imide and lithium trifluoromethylsulfonate, lithium bis(fluorosulfonyl)imide, and lithium perchlorate; the organic solvent includes one or a mixture of any proportion of cyclic carbonates, linear carbonates, carboxylates, and cyclic lactones.

[0012] Further preferably, the electrolyte also includes one or more of a functional additive, a SEI film former, an anti-overcharge additive, a flame retardant and a stabilizer; wherein the functional additive is a mixture of (perfluorobutylsulfonyl) lithium imide and cucurbitacin in a mass ratio of 10:1; the SEI film former is one or more of vinyl carbonate, fluoroethylene, vinyl chloride, propane sultone, butane sultone, tetraalkyl-dienyl siloxane and (p-vinylbenzenesulfonyl) (perfluoroalkylsulfonyl) imide salt.

[0013] Preferably, the diaphragm is a polypropylene-based porous composite diaphragm with a thickness of 20 to 35 microns.

[0014] Further preferably, the diaphragm includes a coating, and the coating includes an inorganic coating or an organic coating; the coating does not contain graphene, graphite and carbon nanotubes.

[0015] More preferably, the inorganic coating includes one or more of Al2O3, Mg(OH)2, SiO2, ZrO2, TiO2 and boehmite.

[0016] More preferably, the organic coating includes one or more of PVDF, PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), PEO (polyethylene oxide), PAN (polyacrylonitrile), PMMA, PVB (polyvinyl butyral), PDA (polydopamine) and polystyrene-acrylate.

[0017] Compared with the prior art, the beneficial effects of the present invention include: The present invention applies an external electric field between electrodes by adopting an electrowetting microfluidic method. An induced electric field will appear in the dielectric layer at the interface between the electrode and the electrolyte, thereby changing the electrostatic interaction between the charged ions in the dielectric layer, and increasing the interaction between the electrode and the electrolyte by regulating the electrostatic interaction between the double layer charge and the ions in the electrolyte, so that the liquid level of the electrolyte in the electrode capillary rises significantly, thereby improving the wetting ability of the liquid electrolyte in the porous electrode, accelerating the wettability between the positive and negative electrodes and the electrolyte, controlling the electrolyte to have a uniform wetting distribution in the electrode piece, and accelerating the wetting rate of the electrode material of the deep-sea high-rate lithium-ion battery. The method of the present invention has excellent wetting performance and high efficiency. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0019] Deep-sea 20-30C high-rate lithium-ion batteries are usually large-capacity, high-energy-density soft-pack batteries of more than 40Ah. Compared with conventional lithium-ion battery electrodes, they have higher compaction density, thicker electrode thickness and three-dimensional elastic diaphragm to meet the pressure of 10,000 meters in the deep sea and high-rate discharge performance. Therefore, the electrode requires a longer infiltration time during the electrolyte infiltration process; the porous electrodes of deep-sea 20-30C high-rate lithium-ion batteries have the characteristics of high compaction density, uneven pore size, high pore size tortuosity, large random pore distribution, and thick electrode. In addition, the surface energy differences between active materials, binders, conductive agents, and current collectors are significant. These factors may lead to poor wettability of electrolytes on battery electrode materials and low wetting efficiency; and poor wetting performance may make it impossible for the electrolyte to evenly cover the electrode surface, resulting in limited electrochemical reactions in local areas, affecting the overall performance of the battery, especially the electrode conductivity.

[0020] In view of the above problems, the present invention can fully improve the electrolyte infiltration efficiency and enhance the high-rate discharge capability through the electrowetting microfluidic method.

[0021] In a first aspect, the present invention provides a microfluidic method for electrowetting of electrode materials for deep-sea high-rate lithium-ion batteries, comprising the following steps: (1) Assemble the electrode material and diaphragm of the lithium-ion battery and inject the electrolyte after the assembly is completed; (2) Apply an external electric field between the electrodes to complete the infiltration of the electrolyte into the lithium-ion battery electrode material.

[0022] Preferably, the voltage of the external electric field is between 100 and 300 mV. If the voltage of the external electric field is too small, it is not conducive to improving the wetting efficiency, while if the voltage of the external electric field is too large, the improvement of the wetting efficiency is not obvious.

[0023] Preferably, the infiltration time is 2 to 3 hours.

[0024] Preferably, the lithium-ion battery is a lithium iron phosphate soft-pack battery.

[0025] Preferably, the electrolyte comprises a lithium salt and an organic solvent.

[0026] Further preferably, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium bis(trifluoromethylsulfonyl)imide and lithium trifluoromethylsulfonate, lithium bis(fluorosulfonyl)imide, and lithium perchlorate; the organic solvent includes one or a mixture of any proportion of cyclic carbonates, linear carbonates, carboxylates, and cyclic lactones.

[0027] The electrolyte of the present invention may also add other raw materials according to the situation, such as functional additives composed of a mixture of (perfluorobutylsulfonyl) lithium imide and cucurbitacin in a mass ratio of 10:1, SEI film formers, anti-overcharge additives, flame retardants and / or stabilizers, etc.; wherein the SEI film former is one or more of vinyl carbonate, fluoroethylene, vinyl chloride, propane sultone, butane sultone, tetraalkyl-dienylsiloxane and (p-vinylbenzenesulfonyl) (perfluoroalkylsulfonyl) imide salts.

[0028] Preferably, the diaphragm is a polypropylene-based porous composite diaphragm with a thickness of 20 to 35 microns.

[0029] Further preferably, the diaphragm includes a coating, and the coating includes an inorganic coating or an organic coating; the coating does not contain three-dimensional conductive structures or particles such as graphene, graphite, and carbon nanotubes.

[0030] More preferably, the inorganic coating includes inorganic substances such as Al2O3, Mg(OH)2, SiO2, ZrO2, TiO2, and boehmite.

[0031] More preferably, the organic coating includes polymers such as PVDF, PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), PEO (polyethylene oxide), PAN (polyacrylonitrile), PMMA, PVB (polyvinyl butyral), PDA (polydopamine), polystyrene-acrylate, etc.

[0032] The main mechanism of action and advantages of the present invention: There are a large number of micro-nano pores in the positive and negative electrode materials of the pressure-resistant lithium battery, forming capillaries; the present invention adopts an electrowetting microfluidic method, that is, an external electric field is applied between the electrodes, an induced electric field will appear in the dielectric layer at the interface between the electrode and the electrolyte, and the surface charge state of the electrode particles changes, thereby changing the electrostatic interaction between the charged ions in the dielectric layer. Through electric field microfluidics, the electrolyte level in the electrode capillary is significantly increased, thereby increasing the penetration / infiltration speed of the electrolyte inside the electrode when the electrolyte is injected to activate the battery, thereby improving the electrode conductivity, which is beneficial to high-power discharge of the battery and is convenient for application in the infiltration of electrode materials for deep-sea high-rate lithium-ion batteries.

[0033] The present invention is further described in detail below through specific examples.

[0034] Example 1 A deep-sea high-rate lithium-ion battery electrode material electrowetting microfluidic method, comprising the following steps: (1) The electrode material and diaphragm of a lithium-ion battery are assembled, and the electrolyte is injected after the assembly is completed; the lithium-ion battery used is a lithium iron phosphate soft-pack battery, which can meet the discharge requirements of 100MPa, 20-30C high rate, and large capacity and high energy density of more than 40Ah. Among them, the electrolyte is a 1mol / L lithium hexafluorophosphate ethylene carbonate solution (also added with 10wt% FEMC and 3% EC), and the diaphragm is a deep-sea special polypropylene-based porous composite diaphragm.

[0035] (2) An external electric field is applied between the electrodes, and the lithium-ion battery electrode material is immersed in the electrolyte for 2 hours; wherein the applied external field voltage is 100 mV.

[0036] Example 2 The only difference from Example 1 is that the applied external field voltage is adjusted to 150 mV, and the other steps and conditions are the same as those in Example 1.

[0037] Example 3 The only difference from Example 1 is that the applied external field voltage is adjusted to 200 mV, and the other steps and conditions are the same as those in Example 1.

[0038] Example 4 The only difference from Example 1 is that the applied external field voltage is adjusted to 250 mV, and the other steps and conditions are the same as those in Example 1.

[0039] Example 5 The only difference from Example 1 is that the applied external field voltage is adjusted to 300 mV, and the other steps and conditions are the same as those in Example 1.

[0040] Comparative Example 1 The only difference from Example 1 is that the applied external field voltage is adjusted to 0 mV (ie, no external electric field is applied), and the other steps and conditions are the same as those in Example 1.

[0041] An electrochemical workstation was used to apply an electric field to the positive and negative electrodes. The effect of the same deep-sea pressure-resistant electrolyte on the wetting rate of the positive electrode of the pressure-resistant lithium iron phosphate battery was tested by using different external electric fields. The results are shown in Table 1.

[0042] Table 1 Wetting effect under different external field voltages

[0043] It can be seen from Table 1 that after the electric field is applied, under the same other conditions, as the voltage increases, the wetting area increases from 3.61 cm in Comparative Example 1 to 2 The wetted area increased significantly, reaching 8.94 cm when the external field voltage was 100 mV. 2 , which is 2.5 times that of comparative example 1; after further increasing the external field voltage, the growth rate of the wetting area slows down, so the preferred external field voltage of the present invention is 100-300mV, and more preferably 100-200mV.

[0044] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A deep-sea high-rate lithium-ion battery electrode material electrowetting microfluidic method, characterized in that: The following steps are involved: (1) Assemble the electrode material and diaphragm of the lithium-ion battery and inject the electrolyte after the assembly is completed; (2) Apply an external electric field between the electrodes to complete the infiltration of the electrolyte into the lithium-ion battery electrode material.

2. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 1, characterized in that: The voltage of the external electric field is between 100 and 300 mV.

3. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 1, characterized in that: The infiltration time is 2 to 3 hours.

4. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 1, characterized in that: The lithium-ion battery is a lithium iron phosphate soft-pack battery.

5. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 1, characterized in that: The electrolyte includes a lithium salt and an organic solvent.

6. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 5, characterized in that: The lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium bis(trifluoromethylsulfonyl)imide and lithium trifluoromethylsulfonate, lithium bis(fluorosulfonyl)imide, and lithium perchlorate; the organic solvent includes one or a mixture of any proportion of cyclic carbonates, chain-like linear carbonates, carboxylates, and cyclic lactones.

7. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 5, characterized in that: The electrolyte also includes one or more of a functional additive, a SEI film former, an anti-overcharge additive, a flame retardant and a stabilizer; wherein the functional additive is a mixture of (perfluorobutylsulfonyl) lithium imide and cucurbitacin in a mass ratio of 10:1; the SEI film former is one or more of vinyl carbonate, fluoroethylene, vinyl chloride, propane sultone, butane sultone, tetraalkyl-dienyl siloxane and (p-vinylbenzenesulfonyl) (perfluoroalkylsulfonyl) imide salt.

8. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 1, characterized in that: The diaphragm is a polypropylene-based porous composite diaphragm with a thickness of 20 to 35 microns.

9. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 8, characterized in that: The diaphragm includes a coating, which includes an inorganic coating or an organic coating; the coating does not contain graphene, graphite and carbon nanotubes.

10. The electrowetting microfluidic method for deep-sea high-rate lithium-ion battery electrode materials according to claim 9, characterized in that: The inorganic coating includes one or more of Al2O3, Mg(OH)2, SiO2, ZrO2, TiO2 and boehmite; the organic coating includes one or more of PVDF, PVDF-HFP, PEO, PAN, PMMA, PVB, PDA and polystyrene-acrylate.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery diaphragm

    CN104821381A

  • A lithium ion power battery pressure sensitive composite separator

    CN109004164A

  • Composite diaphragm as well as preparation method and application thereof

    CN113178663A

  • Electrode infiltration method, lithium ion battery cell and lithium ion battery

    CN114824531A

  • Rapid evaluation method for infiltration effect of battery cell

    CN115792663A